2018
DOI: 10.3390/s18103482
|View full text |Cite
|
Sign up to set email alerts
|

A LN/Si-Based SAW Pressure Sensor

Abstract: Surface Acoustic Wave (SAW) sensors are small, passive and wireless devices. We present here the latest results obtained in a project aimed at developing a SAW-based implantable pressure sensor, equipped with a well-defined, 30 μm-thick, 4.7 mm-in-diameter, Lithium Niobate (LN) membrane. A novel fabrication process was used to solve the issue of accurate membrane etching in LN. LN/Si wafers were fabricated first, using wafer-bonding techniques. Grinding/polishing operations followed, to reduce the LN thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…SAW devices are also good candidates for pressure and temperature sensing [ 63 , 64 , 65 , 66 ]. In the Rodríguez-Madrid et al [ 66 ] study, a SAW-based pressure sensor was reported with a sensitivity of 0.33 MHz/bar, a working frequency between 10 to 14 GHz with high-order harmonic acoustic modes.…”
Section: Current Applicationsmentioning
confidence: 99%
“…SAW devices are also good candidates for pressure and temperature sensing [ 63 , 64 , 65 , 66 ]. In the Rodríguez-Madrid et al [ 66 ] study, a SAW-based pressure sensor was reported with a sensitivity of 0.33 MHz/bar, a working frequency between 10 to 14 GHz with high-order harmonic acoustic modes.…”
Section: Current Applicationsmentioning
confidence: 99%
“…Alternately, when the SAWs reach grating reflectors, they get reflected back to the emitting IDT for RF signal processing (Figure 20b) [228,229]. SAW-based sensing is accomplished by measuring changes in the phase velocity and/or amplitude of the waves caused by property changes in the propagation path such as temperature, mass, electrical, and mechanical changes; therefore, SAW sensors can be employed for monitoring many physical parameters (e.g., temperature [213,230,231,232], pressure [233,234], and strain [235,236]) as well as chemical species in the gaseous and aqueous phases. Detailed reviews on fundamentals of sensing mechanisms and applications can be found in References [228,229,237].…”
Section: Emerging Corrosion Sensing Technologiesmentioning
confidence: 99%
“…Surface acoustic wave sensor (SAW) is a microelectromechanical system (MEMS) that utilizes the propagation of acoustic waves to detect the presence and concentration of the analyte. SAW sensors are extensively used for detecting physical quantities such as strain, pressure, and temperature [3][4][5][6] . Among different gas detection sensors, SAW exhibits excellent response time, small size, low cost, ability to work in wired and wireless mode, and is mainly compatible with modern fabrication technologies.…”
Section: Introductionmentioning
confidence: 99%